2018
DOI: 10.1002/app.47183
|View full text |Cite
|
Sign up to set email alerts
|

Development of highly conductive graphite‐/graphene‐filled polybenzoxazine composites for bipolar plates in fuel cells

Abstract: Superior conductive fillers reinforced polymer composites are ideal alternatives to graphitic and metallic materials in proton exchange membrane fuel cells (PEMFCs) for high thermal and electrical conductive bipolar plates. Polymer composites are known to be adversely influenced from high contact resistance thus to minimize such resistance, highly graphite‐/graphene‐filled polybenzoxazine (PBA) composites are developed in this work. A very low melt viscosity of benzoxazine resin with graphite loading as high a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 40 publications
1
34
0
1
Order By: Relevance
“…Graphite composites with thermoplastic or thermoset materials as matrix are suitable for different applications including bipolar plate materials due to the low corrosion resistance, light weight, and economic production . HDPE is a suitable matrix material for the preparation of polymer composites in particular .…”
Section: Introductionmentioning
confidence: 99%
“…Graphite composites with thermoplastic or thermoset materials as matrix are suitable for different applications including bipolar plate materials due to the low corrosion resistance, light weight, and economic production . HDPE is a suitable matrix material for the preparation of polymer composites in particular .…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 ] With the addition of graphene, graphite‐/graphene‐polymer composite performs better properties compared with graphite‐polymer composite under the same filler content. [ 26 ] That is to say, it would be more effective to fabricate high‐performance polymer composites with graphene instead of graphite. In our previous study, [ 27 ] interlayer polymerization strategy was reported to synthesize graphene‐polymer composites without the exfoliation from chemical expanded graphite (CEG) to graphene.…”
Section: Introductionmentioning
confidence: 99%
“…Although benzoxazine resin has various advantages as described above, it needs to be modified to broaden its range of applications. There are two main strategies for modification of benzoxazines: (1) selection of different phenolics and amines to alter the performance of benzoxazine resin and (2) preparation of composite materials by blending or copolymerizing with other materials …”
Section: Introductionmentioning
confidence: 99%
“…There are two main strategies for modification of benzoxazines: (1) selection of different phenolics and amines to alter the performance of benzoxazine resin and (2) preparation of composite materials by blending or copolymerizing with other materials. [19][20][21][22][23][24][25][26] However, most of the raw materials used for the synthesis of benzoxazine are derived from petroleum resources. To protect the environment and mitigate the depletion of petroleum resources, the use of renewable resources has become an important topic in various fields.…”
Section: Introductionmentioning
confidence: 99%